Operative Behandlung der Dupuytren-Beugekontraktur: Arthrolyse des Fingermittelgelenks - Hohendorff, Bernd; Unglaub, Frank (Der Orthopäde, 2017)
Background: In the operative treatment of Dupuytren’s disease, in certain cases proximal interphalangeal joint flexion contracture remains after fasciectomy due to shrinkage, shortening, and/or adhesion of the periarticular structures. Objectives: How can a residual flexion contracture of the proximal interphalangeal joint after partial fasciectomy in Dupuytren’s disease be treated surgically and what follow-up results can be expected? Methods: Description of anatomy, indication, surgical technique of arthrolysis of the proximal interphalangeal joint, postoperative treatment, and critical analysis of the results reported in the literature. Results: Arthrolysis of the proximal interphalangeal joint is performed in up to six consecutive steps. An improvement of only about 50% compared to preoperative flexion contracture can be expected. Conclusions: Despite alleged unsatisfactory results arthrolysis of the proximal interphalangeal joint can be recommended in surgery of Dupuytren’s disease. In certain cases, patient cooperation during lengthy postoperative treatment is necessary.
Gesehen am 11.10.2018